Strategic management : total quality and global competition - Stahl, Michael J.; Grigsby, David W. (Cambridge, MA : Blackwell, 1997)
Strategic management decisions for total quality and global competition. The environment and the strategic plan. International strategic decisions. Business ethics and corporate social responsibility. Corporate strategy. Business-level strategy: competitive strategy. Business-level strategy: total quality and customer value strategy. Functional strategy. Functional strategy. Strategy implementation: structure and teams. Strategy implementation: culture and behavior. Evaluation, control, and process improvement.
Keywords: Management; Strategic planning; Total quality management; Strategic planning